1999
DOI: 10.1097/00006534-199906000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Digital Two-Dimensional Photogrammetry: A Comparison of Three Techniques of Obtaining Digital Photographs

Abstract: Three methods of obtaining digital photographs in a clinical setting were compared using direct anthropometry as a reference standard. The methods included a digital camera, scanning negatives from a 35-mm single-lens reflex camera, and scanning Polaroid photographs taken with a Polaroid camera designed for medical documentation. A total of 11 angular and linear anthropometric measurements obtained from 30 healthy volunteers were used for the comparison. The data were analyzed using a variance covariance appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 17 publications
1
44
0
6
Order By: Relevance
“…Direct measurements in the thoracic region may be of relative accuracy due to the contour of the body (i.e., curves, prominences and depressions) and movements of the thoracic wall during breathing, which may vary in the same individual at different moments 7,14 . In order to minimize the effects of breathing, Agbenorku et al 18 proposed the use the lowest value of two successive measurements taken with a tape measure in the breast region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct measurements in the thoracic region may be of relative accuracy due to the contour of the body (i.e., curves, prominences and depressions) and movements of the thoracic wall during breathing, which may vary in the same individual at different moments 7,14 . In order to minimize the effects of breathing, Agbenorku et al 18 proposed the use the lowest value of two successive measurements taken with a tape measure in the breast region.…”
Section: Discussionmentioning
confidence: 99%
“…Ward 6 compared measurements of the nose and found no significant differences between direct and indirect anthropometry. Nechala et al 7 reported no differences in angular measurements and linear measurements of two points in the same sagittal plane between photogrammetric measurements and direct anthropometry. Sivagnanavel et al 8 and Assunção et al 9 conducted studies to validate software packages by comparing indirect anthropometric measurements obtained with the different software, arguing that although these digital tools are based on the same theoretical principles they could generate different results.…”
Section: Introductionmentioning
confidence: 97%
“…In 1949, Tanner and Weiner [13] suggested the importance of photogrammetry in medical assessments, which was followed by similar reports [1,2,14,15]. The importance of some type of calibration in the image was emphasized by Mulliken and Sullivan [10].…”
Section: Discussionmentioning
confidence: 99%
“…We think that this is the principal point of importance that was suggested by many authors who studied various kinds of anthropometric measurements. The diameter of a geometric sphere, unlike a flat ruler [2], does not fluctuate according to the viewing angle; therefore, it is an adequate calibrator. Price OD, object distances; en, endocanthion; ex, exocanthion; Rt., right; Lt., left; CD, corneal diameter; A-L, artificial landmark of the steel rod; DM, value of the direct measurement; Df, the difference; Df-Av, the average of 5 Df; %Df-Av, the percentage difference of Df-Av.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation